Streamlining quantitative joint-wide medial femoro-tibial histopathological scoring of mouse post-traumatic knee osteoarthritis models - Haubruck, Patrick; Heller, Raban; Blaker, Carina L.; Clarke, Elizabeth C.; Smith, Susan M.; Burkhardt, Daniel; Liu, Yolanda; Stoner, Shihani; Zaki, Sanaa; Shu, Cindy C.; Little, Christopher B. (Osteoarthritis and cartilage, 2023)
Objectives - Histological scoring remains the gold-standard for quantifying post-traumatic osteoarthritis (ptOA) in animal models, allowing concurrent evaluation of numerous joint tissues. Available systems require scoring multiple sections/joint making analysis laborious and expensive. We investigated if a single section allowed equivalent quantitation of pathology in different joint tissues and disease stages, in three ptOA models. - Method - Male 10-12-week-old C57BL/6 mice underwent surgical medial-meniscal-destabilization, anterior-cruciate-ligament (ACL) transection, non-invasive-ACL-rupture, or served as sham-surgical, non-invasive-ACL-strain, or naïve/non-operated controls. Mice (n = 12/group) were harvested 1-, 4-, 8-, and 16-week post-intervention. Serial sagittal toluidine-blue/fast-green stained sections of the medial-femoro-tibial joint (n = 7/joint, 84 µm apart) underwent blinded scoring of 40 histology-outcomes. We evaluated agreement between single-slide versus entire slide-set maximum or median scores (weighted-kappa), and sensitivity/specificity of single-slide versus median/maximum to detect OA pathology. - Results - A single optimal mid-sagittal section showed excellent agreement with median (weighted-kappa 0.960) and maximum (weighted-kappa 0.926) scores. Agreement for individual histology-outcomes was high with only 19/240 median and 15/240 maximum scores having a weighted-kappa ≤0.4, the majority of these (16/19 and 11/15) in control groups. Statistically-significant histology-outcome differences between ptOA models and their controls detected with the entire slide-set were reliably reproduced using a single slide (sensitivity >93.15%, specificity >93.10%). The majority of false-negatives with single-slide scoring were meniscal and subchondral bone histology-outcomes (89%) and occurred in weeks 1-4 post-injury (84%). - Conclusion - A single mid-sagittal slide reduced the time needed to score diverse histopathological changes by 87% without compromising the sensitivity or specificity of the analysis, across a variety of ptOA models and time-points.
Gesehen am 31.05.2024